Post a New Question


posted by on .

Balance each of the following skeleton equations.

A) KCl + Pb(NO3)2 -> PbCl2 + KNO3

I balanced it out like this.

KCl2 + Pb(NO3)2 -> PbCl2 + 2KNO3

After knowing if I've done this correctly, I'll post on my other questions.

  • Chemistry - ,

    You have balanced it by changing subscripts and that is a no, no.
    2KCl + Pb(NO3)2 ==> PbCl2 + 2KNO3

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question